Why'd they wear that? : fashion as the mirror of history - Albee, Sarah (National Geographic, 2015)
Move over Project Runway. Get ready to chuckle your way through centuries of fashion dos and don'ts! In this humorous and approachable narrative, kids will learn about outrageous, politically-perilous, funky, disgusting, regrettable, and life-threatening creations people have worn throughout the course of human history, all the way up to the present day. From spats and togas to hoop skirts and hair shirts, why people wore what they did is an illuminating way to look at the social, economic, political, and moral climates throughout history.